An octacoordinated Nb atom in the NbAl8H8+ cluster. Issue 75 (6th September 2021) - Ferrari, Piero; Pham, Hung Tan; Vanbuel, Jan; Nguyen, Minh Tho; Fielicke, André; Janssens, Ewald
Abstract : Combined mass spectrometry, infrared spectroscopy, and computational modelling work revealed a unique high-symmetric structure of NbAl8 H8 + . Abstract : The NbAl8 H8 + cluster was formed in a molecular beam and characterized by mass spectrometry and infrared spectroscopy. Density functional theory calculations show the lowest-energy isomer is a high symmetry singlet with the Nb atom placed at the center of a distorted hexagonal Al ring and coordinated by two AlH moieties, therefore exhibiting octacoordination. The unprecedented high-symmetric geometry is attributed to the 20 valence electrons; the central Nb atom adheres to the 18-electron rule and two additional delocalized electrons stabilize the hexagonal ring.